2011
DOI: 10.1038/eye.2011.222
|View full text |Cite
|
Sign up to set email alerts
|

Plaque radiotherapy treatment with ruthenium-106 for iris malignant melanoma

Abstract: Purpose To report the results of ruthenium-106 plaque radiotherapy for iris malignant melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 9 publications
0
17
0
4
Order By: Relevance
“…At our evaluation, best-corrected visual acuity of the involved eye at presentation with the suspicious conjunctival lesion was 20/20 in 2 cases, 20/30 in another and light perception (LP) in a fourth case, and median intraocular pressure (IOP) was 14mmHg (mean: 13, range: [12][13][14]. Examination of the suspicious conjunctival lesions revealed a single small (<5mm in diameter) red lesion in one case, large single multilobed pink lesion in another, and several small pigmented lesions in 2 cases.…”
Section: Clinical Findings and Managementmentioning
confidence: 77%
“…At our evaluation, best-corrected visual acuity of the involved eye at presentation with the suspicious conjunctival lesion was 20/20 in 2 cases, 20/30 in another and light perception (LP) in a fourth case, and median intraocular pressure (IOP) was 14mmHg (mean: 13, range: [12][13][14]. Examination of the suspicious conjunctival lesions revealed a single small (<5mm in diameter) red lesion in one case, large single multilobed pink lesion in another, and several small pigmented lesions in 2 cases.…”
Section: Clinical Findings and Managementmentioning
confidence: 77%
“…В последние годы появились сведения об использовании лучевых методов лечения больных с вышеуказанной патологией [11,[13][14][15][16][17][18][19][20]. Некоторые авторы демонстрируют высокую эффективность и относительную безопасность локального облучения опухоли с использованием радиоактивных офтальмоаппликаторов.…”
Section: оригинальные статьиunclassified
“…Finger et al 18 used palladium-103 plaque therapy for iris and ciliary body melanoma and achieved 100% control. Tsimpida et al 19 and Razzaq et al 20 have demonstrated success with ruthenium-106 ( 106 Ru) plaque therapy.…”
Section: Introductionmentioning
confidence: 99%